Implementasi Nilai Pendidikan Multikultural pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti dalam Meningkatkan Toleransi Siswa - Ria Rizki Ananda (Lembaga Sosial Rumah Indonesia, 2021)
This research is a qualitative research, taking the background of SD Negeri Sinduadi 1 Mlati. Data collection was carried out by conducting observations, interviews, and documentation. The data analysis method used in this research is data reduction, data presentation, and conclusion drawing. Test the validity of the data in this study using triangulation techniques. The results showed that the implementation of the value of multicultural education in Islamic education learning and character had an impact on increasing the tolerance attitude of students at SD Negeri Sinduadi 1 Mlati. Its implementation is done through habituation and exemplary of PAI and BP teachers, besides that also through subject matter related to multicultural education. The results that have been achieved are shown through respecting the rights of each person, the beliefs of others, agreeing on differences, mutual understanding, awareness, honesty, and being helpful. These results can be achieved well because of the supporting factors, namely: teacher personality, school community togetherness, school facilities and activities that support the implementation of multicultural education values ??such as flag ceremonies, scouts, sacrifices, breaking the fast together, 17 August events. Apart from supporting factors, there are also inhibiting factors, namely the condition of the surrounding environment and also the individual characteristics of students.